KONSUMSI BAHAN BAKAR PADA MOBIL KIJANG KF40 MENGGUNAKAN PENGAPIAN KONVENSIONAL PLATINA DENGAN SISTEM PENGAPIAN CDI (CAPASITOR DISCHARGE IGNITION) - i puji setiawan, Deni; Anam, Khoirul (Universitas Muhammadiyah Pekajangan Pekalongan, 2021)
In the development of the ignition system, the conventional ignition system will be marginalized and may not be used anymore because it is considered ineffective. What was originally using a conventional platinum ignition system on the Kijang kf40 car can be replaced or modified with a CDI electronic ignition system, in which here there are slight changes and additional components. This electronic ignition system for conventional vehicles is called the